A picture archiving and communications system featuring multiple monitors using Windows98...Proccedings of the 16th Symposium for Computer Applications in Radiology. 'PACS: Performance Improvement in Radiology.' Houston TX, May 6-9, 1999 - Ernst R; Le VT; Kawashima A; Caskey C; Zelitt D; Tamm E; Sandler CM (Journal of Digital Imaging)
We present an effective approach to manage, review, and distribute Digital Imaging and Communications in Medicine (DICOM) images with multiple monitors using Windows98 (Microsoft Corp, Redmond, WA) that can be implemented in an office-based setting. Computed tomography (CT), magnetic resonance imaging (MRI), and angiographic DICOM images were collected, compressed, and stored using Medweb (Medweb, Inc, San Francisco, CA) software. The Medweb server used the Linux/UNIX operating system on a Pentium 333-MHz processor with 128 MB of RAM. Short-term storage capacity was about 2 weeks with routine usage of an 11-GB hard drive. Images were presented for reading on a dual-monitor Windows98 Pentium display station with 160 MB of RAM using a Medweb/Netscape (Netscape Communications Corp, Mountain View, CA) viewer. There was no significant discrepancy in diagnosis between electronic and conventional film images. Mean reading time for 32 cases was 118 seconds. The Medweb JAVA plug-in viewer loaded the first image within 30 seconds of selecting the case for review. Full uncompressed 16-bit images allowed different window settings to better assess for pathology. Multiple monitors allowed viewing various hanging protocols. Cine viewing was also possible. Key diagnostic images were electronically transmitted to referring physicians. On-call radiologists were able to access images through the Internet. By combining Medweb, DICOM, and web-browser software using desktop personal computers (PCs), an easily accessible picture archiving and communications system (PACS) is available to radiologists and referring physicians. Multiple monitors are easily configured and managed using Windows98. This system can sustain changes and can be extended to provide variable functions using inexpensive PCs. Copyright (c) 1999 by W.B. Saunders Company